ANALISIS IMPLEMENTASI HEARING CONSERVATION PROGRAM DI PT KALTIM PRIMA COAL - Ilham Maulana; Siswi Jayanti; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Hearing Conservation Program is an ongoing program which aims to prevent hearing loss due to noise in the workplace. Mining process uses multi open pit mining method which involves a lot of heavy equipment with a variety of function, sizes, and types. The purpose of this study was to analyze compliance and quality of implementation of Hearing Conservation Program in PT. Kaltim Prima Coal compared with the applicable regulations and standards. The type of this research was descriptive with the qualitative approach. There were nine workers who participated in this study. Triangulation in this study was the results of indepth interviews with triangulation informants, observation, and applicable standards. The results showed that PT. Kaltim Prima Coal complied 78,6 percent of the required criteria of OSHA and NIOSH elements such as policies, resources, surveys noise, technical and administrative noise control, education and motivation, ear protection, hearing acuity monitoring, recording, and reporting, evaluation, and audit program; while 21,4 percent had not complied. In conclusion, the implementation of hearing conservation program in PT. Kaltim Prima Coal had been good enough. PT. Kaltim Prima Coal should do the noise mapping based on noise exposure dose.